2017
DOI: 10.1002/14651858.cd008680.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent auscultation (IA) of fetal heart rate in labour for fetal well-being

Abstract: Intermittent auscultation (IA) of fetal heart rate in labour for fetal well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…Short-term outcomes include stillbirth, low Apgar score, need for resuscitations, neonatal intensive care unit admissions, and early neonatal deaths. 6 Long-term outcomes include cognitive and behavioral disabilities – affecting perhaps as much as one million children each year. 7 , 8 A focus on high coverage of good quality care during birth, including timely identification and rescue of the fetus from intrapartum hypoxia, 9 will save the lives of many newborns.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term outcomes include stillbirth, low Apgar score, need for resuscitations, neonatal intensive care unit admissions, and early neonatal deaths. 6 Long-term outcomes include cognitive and behavioral disabilities – affecting perhaps as much as one million children each year. 7 , 8 A focus on high coverage of good quality care during birth, including timely identification and rescue of the fetus from intrapartum hypoxia, 9 will save the lives of many newborns.…”
Section: Introductionmentioning
confidence: 99%
“…Auscultation with a fetal stethoscope, and occasionally with a fetal Doppler, are often the only method of fetal monitoring available in many low-resource settings [ 22 , 23 ]. In high-resource countries, cardiotocograph (CTG) is used, but complexities including high cost and need to continuous electricity supply limit use in low-resource settings [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…found that fetal heart rate (FHR) abnormalities detected during labor are associated with fresh stillbirth, low Apgar scores, and neonatal deaths . FHR monitoring during labor is the gold standard for facilitating improved fetal and neonatal outcomes . Proper and adequate monitoring of FHR using sensitive and reliable devices, coupled with timely and appropriate obstetric responses, can dramatically reduce the incidence of intrapartum‐related hypoxia, FSB, and neonatal deaths…”
Section: Introductionmentioning
confidence: 99%